Methylome analyses of three glioblastoma cohorts reveal chemotherapy sensitivity markers within DDR genes. (29th September 2020) - Kessler, Tobias; Berberich, Anne; Sadik, Ahmed; Sahm, Felix; Gorlia, Thierry; Meisner, Christoph; Hoffmann, Dirk C.; Wick, Antje; Kickingereder, Philipp; Rübmann, Petra; Bendszus, Martin; Opitz, Christiane; et al.
Abstract: Background: Gliomas evade current therapies through primary and acquired resistance and the effect of temozolomide is mainly restricted to methylguanin‐O6-methyltransferase promoter (MGMT) promoter hypermethylated tumors. Further resistance markers are largely unknown and would help for better stratification. Methods: Clinical data and methylation profiles from the NOA‐08 (104, elderly glioblastoma) and the EORTC 26101 (297, glioblastoma) studies and 398 patients with glioblastoma from the Heidelberg Neuro‐Oncology center have been analyzed focused on the predictive effect of DNA damage response (DDR) gene methylation. Candidate genes were validated in vitro. Results: Twenty‐eight glioblastoma 5'‐cytosine‐phosphat‐guanine‐3' (CpGs) from 17 DDR genes negatively correlated with expression and were used together with telomerase reverse transcriptase (TERT) promoter mutations in further analysis. CpG methylation of DDR genes shows highest association with the mesenchymal (MES) and receptor tyrosine kinase (RTK) II glioblastoma subgroup. MES tumors have lower tumor purity compared to RTK I and II subgroup tumors. CpG hypomethylation of DDR genes TP73 and PRPF19 correlated with worse patient survival in particular in MGMT promoter unmethylated tumors. TERT promoter mutation is most frequent in RTK I and II subtypes and associated with worse survival. Primary glioma cells show methylation patterns that resemble RTK I and II glioblastoma and long term established glioma cell lines do not match with glioblastoma subtypes. Silencing of selected resistance genes PRPF19 and TERT increase sensitivity to temozolomide in vitro. Conclusion: Hypomethylation of DDR genes and TERT promoter mutations is associated with worse tumor prognosis, dependent on the methylation cluster and MGMT promoter methylation status in IDH wild‐type glioblastoma. Abstract : Hypomethylation of DNA damage response genes correlates with worse survival in glioblastoma patients. Silencing of PRPF19 and TERT in glioblastoma in vitro models increase sensitivity to temozolomide